Preparation of Stable Zein/Poly(γ‐glutamic acid) Nanocomposite Particles for Improved Encapsulation of Curcumin - Jie Mei; Yunxing Li; Yikai Feng; Bingtian Zhao; Cheng Yang; Yajuan Sun; To Ngai (Advanced Materials Interfaces, 2025)
Abstract The aim of this study is to enhance the stability of zein nanoparticles by using poly(γ‐glutamic acid) (γ‐PGA) as a stabilizer. Zein/γ‐PGA nanocomposite particles are produced through a straightforward anti‐solvent precipitation method. The incorporation of γ‐PGA influenced the average particle size, zeta potential, and overall stability of the resulting zein/γ‐PGA nanocomposite particles. These particles exhibit greater resistance to aggregation and sedimentation compared to zein nanoparticles across various environmental conditions, including a wide pH range (3.0–9.0), elevated temperatures (80 °C for 120 min), high ionic strength (1000 mm), and prolonged storage at 4 °C (up to 3 months). Fluorescence spectroscopy reveals significant interactions between zein and γ‐PGA. Fourier transform infrared spectroscopy and zeta potential measurements indicate that hydrogen bonding, hydrophobic interactions, and electrostatic attraction are the primary mechanisms driving these interactions. Importantly, the conditions for forming zein/γ‐PGA nanocomposite particles are effectively utilized to encapsulate a hydrophobic bioactive model (curcumin) with high encapsulation efficiency. The encapsulated curcumin demonstrates improved stability and an amorphous structure compared to free curcumin. Based on these results, zein/γ‐PGA nanocomposite particles can serve as a promising vehicle for hydrophobic active ingredients in food, pharmaceuticals, and cosmetics.